ANALISA DARI PERANCANGAN CAR LIFT SISTEM HIDROLIK MENGGUNAKAN SOFTWARE SOLIDWORKS 2021 - Ariyanto Ariyanto (Asosiasi Dosen Muda Indonesia, 2024)
Car Lift hydraulic system is a form of change or transfer of power by using a conducting medium in the form of liquid fluid to obtain more power than the initial power released. The purpose of this writing is to find out the Car Lift design process for vehicles, as well as the Car lift design testing process using software solidworks 2021. Observation method, literature study method, and simulation method are the references in this writing. Based on the results of the simulations carried out, the smallest von misses value is 6,017 N/mm2 and the largest is 60,174 N/mm2, then for the displacement value obtained the smallest is 0.046 mm and the largest is 0.456 mm, then for the strain value with the pressure value obtained the smallest is 0.00002 and the largest is 0.00019, and the Factor Of Safety value in the design with material (ASTM A36) results in a safety factor of 4.2, the Car Lift design offers a level of reliability that meets recognized industry standards.